ANALISIS RISIKO REAKSI OBAT YANG TIDAK DIKEHENDAKI PADA PASIEN HIPERTENSI GERIATRI DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Septi Muharni; Erniza Pratiwi; Yuwanda Iswari (Jurnal Ilmiah Manuntung, 2019)
Adverse Drug Reaction (ADR) is every adverse event related to the use of a drug in humans. Geriatrics have a 7 times greater risk of developing ADR. Hypertension is the most common disease suffered by geriatric patients. The purpose of this study was to analyze the risk of ADR occurrence in geriatric hypertension patients and also to analyze the relationship of demographic data with the incidence of ADR. This study was carried out in an observational manner which was descriptive analytic with a cross sectional approach in 88 medical record samples of geriatric hypertension patients in inpatient installations using gerontoNET scores. Based on the ADR risk variable according to the gerontoNET score, there was 1 patient with ≥4 comorbid, 45 patients had heart failure, 5 patients had liver disorders, 19 patients received 6-7 drugs and 37 patients received ≥8 drugs, no patients with ADR history, and 28 patients developed kidney problems. From the results of this study, there are 37 patients who have a high risk of ADR events which are marked by gerontoNET score ≥4. Based on the correlation analysis of gender and age range on ADR risk obtained a weak relationship and no significant correlation (r = 0.116, p = 0.116; r = 0.017, p = 0.847), so that gender and age in geriatric hypertension patients are not related to the risk of ADR.